The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1404140
|View full text |Cite
|
Sign up to set email alerts
|

Temporary pain relief using transcranial electrotherapy stimulation: results of a randomized, double-blind pilot study

Abstract: Results of a randomized, double-blind pilot study indicate that transcranial electrotherapy stimulation may be an effective treatment for the temporary reduction of pain in osteoarthritis patients. Presently, the predominant method for pain management is medication. One very different approach is the application of micro- to milliamp current applied to specific areas of the head, resulting in a release of endogenous opioids from pain management regions of the brain. For the pilot study, 64 subjects suffering f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…A previous study using a similar technique over the motor cortex suggests that the cortex may be directly stimulated underlying the active electrode; in our study, it was the premotor frontal cortex 13. A similar pilot study using an identical device to treat pain due to osteoarthritis demonstrated a significant benefit in treated groups compared with sham stimulation 6. Based on this, we do not believe a simple lack of biological effect is responsible for our findings.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…A previous study using a similar technique over the motor cortex suggests that the cortex may be directly stimulated underlying the active electrode; in our study, it was the premotor frontal cortex 13. A similar pilot study using an identical device to treat pain due to osteoarthritis demonstrated a significant benefit in treated groups compared with sham stimulation 6. Based on this, we do not believe a simple lack of biological effect is responsible for our findings.…”
Section: Discussionsupporting
confidence: 47%
“…The Nexalin device is an investigational transcranial electrostimulation device being developed in the United States for the long‐term reduction of pain associated with osteoarthritis of the knee 6. The device utilizes low‐amperage alternating current delivered over the frontal aspect of the scalp bilaterally.…”
mentioning
confidence: 99%
“…For rTMS there were 22 parallel studies (Ahmed 2011; Avery 2013; Boyer 2014; Carretero 2009; Dall'Agnol 2014; Defrin 2007; de Oliveira 2014; Fregni 2011; Khedr 2005; Lee 2012; Malavera 2013; Medeiros 2016; Mhalla 2011; Nardone 2017Passard 2007; Picarelli 2010; Short 2011; Tekin 2014; Tzabazis 2013; Umezaki 2016; Yagci 2014; Yilmaz 2014), and 20 cross‐over studies (André‐Obadia 2006; André‐Obadia 2008; André‐Obadia 2011; Borckardt 2009; Fregni 2005; Hirayama 2006; Hosomi 2013; Irlbacher 2006; Jetté 2013; Kang 2009; Lefaucheur 2001a; Lefaucheur 2001b; Lefaucheur 2004; Lefaucheur 2006; Lefaucheur 2008; Nurmikko 2016; Onesti 2013; Pleger 2004; Rollnik 2002; Saitoh 2007). For CES there were eight parallel studies (Gabis 2003; Gabis 2009; Katsnelson 2004; Lichtbroun 2001; Rintala 2010; Tan 2006; Tan 2011; Taylor 2013), and three cross‐over studies (Capel 2003; Cork 2004; Tan 2000), of which we considered two as parallel studies, with only the opening phase of the study considered in this review because subsequent phases were unblinded (Capel 2003; Cork 2004). For tDCS there were 26 parallel studies (Ahn 2017; Bae 2014…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies investigating CES, one study included participants with pain related to osteoarthritis of the hip and knee (Katsnelson 2004), and two studied chronic back and neck pain (Gabis 2003; Gabis 2009). Of these, the later study also included participants with chronic headache but these data were not considered in this review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation